2019
DOI: 10.1007/s40430-019-1892-7
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and evolutionary computation on drilling of carbon fiber-reinforced polymer nanocomposite: an integrated approach using RSM based PSO

Abstract: Among the various classifications of fiber-reinforced polymer composites, carbon fiber-reinforced plastic (CFRP) composite materials have great potential in aerospace, automobile and marine industries. Drilling is a common machining process of CFRP composites. Surface delamination, tearing, abrasion, denting, cutting of fibers, formation of voids, fiber bending and pullout, etc. are significant problems that occur in the drilling of CFRP composites, among which surface delamination is identified as a critical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Swarm intelligence algorithm is an intelligent bee colony algorithm that simulates bees searching for nectar. These algorithms have several advantages, including high-quality solutions, excellent local search capabilities, and an updated mechanism for solving problems [24,25]. In addition to improving local search capabilities, this also increases swarm stochasticity.…”
Section: Swarm Intelligence Algorithmmentioning
confidence: 99%
“…Swarm intelligence algorithm is an intelligent bee colony algorithm that simulates bees searching for nectar. These algorithms have several advantages, including high-quality solutions, excellent local search capabilities, and an updated mechanism for solving problems [24,25]. In addition to improving local search capabilities, this also increases swarm stochasticity.…”
Section: Swarm Intelligence Algorithmmentioning
confidence: 99%
“…Step 2: The predictive models of the R a , R y , and T M are then developed regarding the process inputs using RSM models [16,17].…”
Section: Optimization Frameworkmentioning
confidence: 99%
“…Singh et al 31 used PSO and bacteria foraging optimization (BFO) to obtain the optimal processing parameters for milling of Inconel 718 alloy, and their results indicated that PSO was more effective. Vijayan et al 32 used response surface method (RSM) hybrid PSO to optimize the parameters for drilling of carbon fiber-reinforced polymer (CFRP). Gupta et al 33 optimized the processing parameters for machining of a nickel-based superalloy by combining PSO with TLBO.…”
Section: Introductionmentioning
confidence: 99%